Developing Culture-Based English Learning Material to Support the Implementation of Curriculum 2013 for the First Semester of Grade Seven Junior High School in Buleleng - A Fitri; I Gede Batan; N W.S Mahayanti (Universitas Pendidikan Ganesha, 2016)
This research aimed at developing culture based English learning material to support the implementation of curriculum 2013 for the first semester of grade seven junior high schools in Buleleng. This research was designed by utilizing an RnD model development proposed by Peffers et al in Ellis and Levy (2010). t. In order to reach the high qualified product, there were two experts evaluated the content of product, integration of local culture, and presentation of culture based English learning material in the form of English judgment form. All data were analyzed quantitatively and qualitatively. The result of this research was designed in the form of culture based English textbook to support the implementation of curriculum 2013 for the first semester of grade seven junior high schools in Buleleng. This textbook consisted of 4 topics. The material was designed carefully depends on Balinese culture context. The context of Balinese culture were integrated into pictures, dialogues, and learning activities. Culture based English textbook were also designed to meet the characteristic of good textbook by Tomlinson (1998). Generally, the two experts stated that the product were already interesting and appropriate with characteristic of good textbook.